English Language Learners' Comprehension of Logical Relationships in Expository Texts: Evidence for the Confluence of General Vocabulary and Text‐Connecting Functions. Issue 3 (19th April 2021) - Fraser, Christie; Pasquarella, Adrian; Geva, Esther; Gottardo, Alexandra; Biemiller, Andrew
Abstract: Conjunctions facilitate text cohesion and comprehension by making explicit the logical relationships between ideas in written language. Conjunctions may be challenging for English language learners (ELLs) because of their novel, abstract, and text‐connecting role. In this longitudinal study we aimed to clarify the connections among comprehension of logical relationships, general vocabulary knowledge, and reading comprehension in elementary school‐aged ELLs. We assessed these skills—along with decoding, working memory, and nonverbal reasoning—in 74 ELLs in Grades 3 and 4. Path analysis revealed that comprehension of logical relationships was a direct predictor of concurrent reading skills in Grades 3 and 4, and an indirect predictor of reading comprehension in Grade 4, where vocabulary and prior comprehension performance acted as partial mediators. Results point to the confluence of general vocabulary with conjunctions in contributing to individual differences in ELLs' reading comprehension. Conjunctions represent a specialized form of vocabulary knowledge that should not be subsumed developmentally or instructionally under general vocabulary knowledge. Abstract :